Jugendsprache: bahasa remaja Jerman pada akun Instagram Funk - Maharani, Inggrid Prinsia; Nugroho, Suray Agung (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
German youth language or Jugendsprache is a language style used by German teenagers and young adults in their daily communication. This language style is adopted by a German content network named Funk in its Instagram account posts to gain attention from its audience, which specifically targets people aged between 14 to 29 years old. The purpose of this research is to investigate the forms of Jugendsprache used by Funk in their Instagram posts. The design of this research is descriptive qualitative. The data corpus in total of 288 sentences was acquired from Funk’s Instagram account. The results unveiled that there were 177 lexicons, 55 word formations and 28 semantic shifts found from the data. Anglicism, in total of 112 data, is the most dominant lexicon phenomenon compared to the others. Another significant process are 29 composition data in word formation and 23 extensions of meaning data in semantic shift. From this research, it was found that English is widely used in Funk’s contents, either in the form of words, phrases, sentences in full English or English words adopted into the German morphological system. Funk utilizes English to make their contents interesting for its’ target audience, the young people.